A sequentially triggered DNA nanocapsule for targeted drug delivery based on pH-responsive i-motif and tumor cell-specific aptamer - Yuan, Baoyin; Xi, Yanan; Qi, Cuihua; Zhao, Mingzhu; Zhu, Xiaoyan; Tang, Jinlu (Frontiers in Bioengineering and Biotechnology, 2022)
Targeted drug delivery with minor off-target effects is urgently needed for precise cancer treatments. Here, a sequentially triggered strategy based on double targeting elements is designed to meet this purpose. By using an acidic pH-responsive i-motif DNA and a tumor cell-specific aptamer as targeting elements, a smart dual-targeted DNA nanocapsule (ZBI5-DOX) was constructed. ZBI5-DOX can be firstly triggered by acidic pH, and then bind to target cells via aptamer recognition and thus targeted release of the carried DOX chemotherapeutics. With this smart DNA nanocapsule, the carried DOX could be precisely delivered to target SMMC-7721 tumor cells in acidic conditions. After drug treatments, selective cytotoxicity of the DNA nanocapsule was successfully achieved. Meanwhile, the DNA nanocapsule had a specific inhibition effect on target cell migration and invasion. Therefore, this sequentially triggered strategy may provide deep insight into the next generation of targeted drug delivery.